Hubungan Bermain Outdoor dengan Regulasi Emosi Anak Usia Dini di TK Serangkai - Marsha Abdullah; Dindayasnatia Dindayasnatia; Nurrahmania Mudin; Siska Ibrahim; Fadila Usman; Mita Sari (INDO PUBLISHING, 2026)
This empirical inquiry is directed toward evaluating the interconnectedness between open-air recreational engagement and the capacity for emotional self-regulation during the early stages of childhood development. Open-air play initiatives are conceptualized as purposeful dynamics that function crucially in accelerating the social-emotional maturation of young learners. By means of these outdoor experiences, children are provided with a platform to articulate their internal affective states, engage responsively with their physical surroundings, adjust to diverse social structures, and refine behavioral competencies across a variety of settings. Direct experiential learning within natural outdoor environments further furnishes a constructive environment for youth to cultivate coping mechanisms and manage affective responses with greater efficiency. To systematically examine the relationship between open-air play routines and early childhood emotional modulation, this investigation utilized a quantitative methodology combined with a correlational research design. The cohort of informants for this study comprised parent-child dyads, with the targeted youth falling within the 4-to-5-year age bracket and actively enrolled in preschool education. Information gathering was executed through the administration of a standardized Likert-scale diagnostic survey distributed directly to the designated cohort. Subsequently, the accumulated dataset underwent statistical computing via the Pearson Product Moment correlation framework to establish the precise magnitude of the relationship between outdoor playtime and the children's emotional command. The descriptive outputs revealed that the intensity of open-air play practices reached an elevated classification. Correspondingly, the children's psychological capacity for regulating their emotions was also categorized at a superior level. Derived from the statistical outputs of the correlational assessment, the evidence confirms that open-air play practices bear a direct and meaningful linkage with emotional adaptation in early youth. Children who maintain a higher frequency of engagement in outdoor recreations demonstrate a strong propensity toward superior emotional oversight, enhanced socialization within community environments, and healthier manifestations of their feelings relative to their immediate situational contexts.These analytical insights indicate that outdoor recreational routines exert a substantial influence on reinforcing emotional maturity during early childhood. Consequently, it is imperative that open-air play opportunities be systematically maintained and structurally advanced within both institutional academic settings and domestic family systems as a foundational pillar in maximizing children's holistic social-emotional progress.